VALUASI HARGA SAHAM PERUSAHAAN SUBSEKTOR TOURISM, RESTAURANT, DAN HOTEL (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022) - Ni Luh Putu Uttari Premananda; Ni Komang Urip Krisna Dewi (UHN IGB Sugriwa Denpasar, 2023)
This study aims to assess the intrinsic value of companies in the subsector of tourism, restaurant, and hotel listed on the Indonesia Stock Exchange (IDX) in the year 2022. The research employs two valuation methods, namely Price to Book Value (PBV) and Discounted Cash Flow (DCF). The research approach used in this study is quantitative. The sampling technique applied is purposive sampling, where companies with positive earnings and equity were selected, resulting in 15 companies being chosen out of a population of 35 companies. The findings of the study reveal that in the year 2022, there were 4 undervalued stocks (trading below their fair value) using the PBV method, and 8 undervalued stocks using the DCF method. These undervalued stocks are recommended for purchase. On the other hand, in the year 2015, there were 11 overvalued stocks (trading above their fair value) using the PBV method, and 7 overvalued stocks using the DCF method. These overvalued stocks are suggested for selling. From the accuracy analysis, it can be observed that the DCF method produces more accurate intrinsic values compared to the PBV method, as indicated by the lower average RMSE of DCF compared to the average RMSE of PBV.